2016
DOI: 10.3389/fnagi.2016.00039
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Cognition in the Ageing Brain: A Brief Review of the Short- and Long-Term Links between Perceptual and Cognitive Decline

Abstract: Ageing is associated with declines in both perception and cognition. We review evidence for an interaction between perceptual and cognitive decline in old age. Impoverished perceptual input can increase the cognitive difficulty of tasks, while changes to cognitive strategies can compensate, to some extent, for impaired perception. While there is strong evidence from cross-sectional studies for a link between sensory acuity and cognitive performance in old age, there is not yet compelling evidence from longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
115
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(136 citation statements)
references
References 81 publications
8
115
1
5
Order By: Relevance
“…Beta‐amyloid peptide deposits and specific genetic risk factors (apolipoprotein E and complement factor H) are present in individuals with dementia and age‐related macular degeneration, and it has been suggested that the 2 disease have a common pathophysiology . In addition, as with hearing loss, vision impairment may impair visual cognition and perception, which could increase cognitive load …”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Beta‐amyloid peptide deposits and specific genetic risk factors (apolipoprotein E and complement factor H) are present in individuals with dementia and age‐related macular degeneration, and it has been suggested that the 2 disease have a common pathophysiology . In addition, as with hearing loss, vision impairment may impair visual cognition and perception, which could increase cognitive load …”
Section: Discussionmentioning
confidence: 75%
“…13,48 In addition, as with hearing loss, vision impairment may impair visual cognition and perception, which could increase cognitive load. 49…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…Older adults often report difficulties when searching for items within cluttered visual scenes . Although some of this age‐related visual decline could be the result of changes in low‐level vision (for example, visual acuity, reduced contrast sensitivity; greater sensitivity to crowding), some age‐related declines in visual information processing also result from decreases in higher‐level visual processes, such as visual attention, memory and inhibitory processes …”
Section: Discussionmentioning
confidence: 99%
“…This concept of a common underlying process shared across all five senses contrasts with prior work examining the effect of specific sensory deficits independently (or in subsets of two or three). 6,15 Instead, GSI measures the intrinsic mechanisms common to deterioration of all the senses, for example, neurophysiological changes associated with aging (e.g., loss of lateral inhibition, decreased specialization of neural pathways and greater connectivity, decrease in white matter density and thinning of the cortex) 45 that are the result of a variety of mechanisms. Thus, decline of the sensory systems would serve as an early harbinger that reflects general neurophysiological decline.…”
Section: Discussionmentioning
confidence: 99%